The Role of Duration of Diabetes in the Development of Diabetic Retinopathy in Young Diabetic Patients in Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2010)
The pathogenesis of diabetic retinopathy is still unclear. The relative role of duration of diabetes have been thought to be factor associated with diabetic retinopathy. A total number of 91 diabetic subjects, diabetes diagnosed before the age of 30 years, was recruited from the outpatient department, BIRDEM Hospital. Diabetic subjects recruited were sub grouped according to the duration of diabetes and presence of diabetic retinopathy was compared. The incidence of retinopathy was highest among the patients with longest duration of diabetes (p=.004) the earlier the age of onset of diabetes the more is the chance of development of diabetic retinopathy. It may be concluded that the duration of diabetes plays a central role in development of diabetic retinopathy in absence of hypertension, hyperlipiedemia and obesity. DOI:10.3329/jbcps.v27i3.4289 J Bangladesh Coll Phys Surg 2009; 27: 1330138